2017
DOI: 10.1111/1742-6723.12844
|View full text |Cite
|
Sign up to set email alerts
|

Patient perspectives on priorities for emergency medicine research: The PERSPEX study

Abstract: The top 5 emergency medicine research priorities nominated by patients in ED were cardiology, trauma, ED processes, mental health and haematology/oncology, although many 'system priorities' were identified as well. These priorities were generally consistent with ACEM researchers, but patients also suggested alternative directions for future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…The Centre for Clinical Research in Emergency Medicine (CCREM) has previously involved ED patients in setting research priorities. We found that ED patients chose priorities that were consistent with ACEM researchers, but patients also suggested alternative directions for future research . In preparation for future funding applications, CCREM researchers worked with The Consumer and Community Health Research Network (CCHRN) to host a community conversation about sepsis.…”
Section: Consumer Involvement Challenges In Emergency Medicine Researchmentioning
confidence: 78%
See 1 more Smart Citation
“…The Centre for Clinical Research in Emergency Medicine (CCREM) has previously involved ED patients in setting research priorities. We found that ED patients chose priorities that were consistent with ACEM researchers, but patients also suggested alternative directions for future research . In preparation for future funding applications, CCREM researchers worked with The Consumer and Community Health Research Network (CCHRN) to host a community conversation about sepsis.…”
Section: Consumer Involvement Challenges In Emergency Medicine Researchmentioning
confidence: 78%
“…One of the best examples of this includes involving those with personal experience of a health condition in formulating outcomes for clinical trials. Public contributors can also help to steer future research priorities, assist with grant applications and the dissemination of results . In 2002 the National Health and Medical Research Council and the Consumer Health Forum jointly released an initial statement setting out their position .…”
Section: Introductionmentioning
confidence: 99%
“…Care of the older person in the emergency department (ED) is a priority area for emergency care research from the perspectives of emergency physicians in the UK [ 1 ] and Australia [ 2 , 3 ], and ED patients [ 4 ]. The need to prioritise the care of older person is underpinned by several challenges including an ageing population (which is evident in every country in the world) [ 5 ] and over-representation of older people in the ED [ 6 ].…”
Section: Introductionmentioning
confidence: 99%